Accrediting learning through experience to provide access to higher education: the case of those over 23 at the university of Lisbon - Belmiro Gil Cabrito (Universidade Federal de Santa Catarina, 2009)
The need to improve education of the labor force in Portugal to reinforce economic competitiveness, led to the implementation of educational policies requiring mandatory schooling until the age of 12. These measures are highlighted by the process of recognition, certification and validation of the abilities acquired by experience. In recent years, Centers of Recognition, Validation and Certification of Abilities have been created, and the government plans to increase the number of centers from 219 to 500 by the year 2010 to traiu one million active workers. Curiously, this recognition of experience has also reached higher education, through decreelaw n° 64/2006, of March 21. Thus, since 2006, workers can be accepted to higher education courses through the accreditation of their experience. This article briefly describes and analyzes how this process took place based on the example of those Maiores de 23 (Over 23) at the University of Lisbon and reflects on its objectives and foundations.